RIBBONFISH FISHERY OF KAKINADA DURING 1974-1976 - Sastry, Y Appanna (Indian Journal of Fisheries, 2011)
The ribbonfi&h fishery of Kakinada during 1974-76 tesed on the landingsby conMnercial trawlers showed that the annual catches varied from 371.6 to 632.4tonnes and on an average formed' 6.3% of the toltal fish catch. Among the sixrilbbonfish species, Trichiurus lepturus dominated and accounted for 73% of thetotal ribbonfish landings. The seasonal abundance and species composition of allthe ribbonfishes; the lecigth-weight relationships in L. gangeticus and T. russelli;and the periodicity of spawning in L. gangeticus are presented in the paper